Evaluation of a Novel Dry Latex Preparation for Demonstration of Infectious Mononucleosis Heterophile Antibody in Comparison with Three Established Tests - Rogers, Richard (American Society for Microbiology, 1999)
A new, dried antigen-coated latex preparation for the demonstration of infectious mononucleosis (IM) heterophile antibody (Dryspot IM kit; Oxoid, Ltd., Basingstoke, Hampshire, United Kingdom) was compared with the IM kit (a liquid latex reagent from the same source), an immunoassay (ImmunoCard Mono; Meridian Diagnostics), and an absorption test (Monospot; Meridian Diagnostics). The latter was used as a standard for initial statistical comparisons. Discrepancies were resolved by using Epstein-Barr virus serology. Of the 328 routine samples tested, 77 were positive and 222 were negative by all IM heterophile antibody-based kits. Twenty-nine samples gave discrepant results. Following resolution of discrepant results, the sensitivity and specificity values for the IM Dryspot kit were 87.0 and 98.7%, those for the Oxoid liquid latex IM kit were 83.0 and 99.6%, and those for the ImmunoCard Mono immunoassay were 85.0 and 100.0%, respectively. The evaluation shows that the Dryspot kit, which is uniquely straightforward to use and may be stored at room temperature, is comparable in performance to other rapid heterophile tests for the confirmation of IM.